Non‐Oxidative Dehydrogenation Pathways for the Conversion of C2–C4 Alcohols to Carbonyl Compounds. Issue 23 (23rd October 2015) - Shylesh, Sankaranarayanapillai; Kim, Daeyoup; Ho, Christopher R.; Johnson, Gregory R.; Wu, Jason; Bell, Alexis T.
Abstract: Gold nanoparticles (NPs) supported on hydrotalcite (Au/HT) are highly active and selective catalysts for the continuous, gas‐phase, non‐oxidative dehydrogenation of bioderived C2 –C4 alcohols. A sharp increase in turn over frequency (TOF) is noted when the size of Au NPs is less than 5 nm relating to the strong synergy between metallic Au NPs and the acid–base groups on the support surface. It is shown that catalytic activity depends critically on Au NP size, support composition, and support pretreatments. A reaction pathway elucidated from kinetic isotope effects suggests that the abstraction of β‐H by Au NPs (C−H activation) is the rate‐determining step in the dehydrogenation of bioderived C2 –C4 alcohols. Abstract : All that′s good is gold : Gold nanoparticles supported on calcined hydrotalcite (Au/HT) are highly active and very selective catalysts for the continuous, gas‐phase, non‐oxidative dehydrogenation of bioderived C2 –C4 alcohols. The authors show that the catalytic activity depends critically on the gold nanoparticle size and the composition and pretreatment of the hydrotalcite support.